2019
DOI: 10.1111/apt.15550
|View full text |Cite
|
Sign up to set email alerts
|

A validated risk stratification tool for detecting high‐risk small bowel Crohn's disease

Abstract: Summary Background Delays in Crohn's disease (CD) diagnosis are positively associated with ileal location and an increased risk of complications. Aim To develop a simple risk assessment tool to enable primary care physicians to recognise potential ileal CD earlier, shortening the delay to specialist investigation Methods Three cohorts were acquired for this study. Cohort 1 included 61 patients retrospectively identified with ileal CD between 2000 and 2010 and 78 matched controls drawn from a cohort referred fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 17 Platelets have been shown to be a good surrogate marker for subacute inflammation, in some instances reflecting inflammatory disease activity better than CRP. 18 , 19 Serum albumin is recognized as a biomarker of chronic bowel injury and reflects multifactorial malnutrition associated with increasingly severe CD. 7 , 20 Interestingly, in our study, the historical behavior of albumin (captured using the albumin PCA) had more importance for predicting surgical outcomes than single time point measurements, suggesting that the temporal context of albumin values over time is an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Platelets have been shown to be a good surrogate marker for subacute inflammation, in some instances reflecting inflammatory disease activity better than CRP. 18 , 19 Serum albumin is recognized as a biomarker of chronic bowel injury and reflects multifactorial malnutrition associated with increasingly severe CD. 7 , 20 Interestingly, in our study, the historical behavior of albumin (captured using the albumin PCA) had more importance for predicting surgical outcomes than single time point measurements, suggesting that the temporal context of albumin values over time is an important consideration.…”
Section: Discussionmentioning
confidence: 99%
“…They found that genetic variants associated with SICD, family history and fecal calprotectin together identified individuals with presymptomatic intestinal inflammation who are therefore at risk for SICD. Shen et al [ 80 ] developed a web-based SICD hazard stratification tool. Predicting high-risk populations for SICD based on altered bowel habit, abdominal pain, white blood cell count, albumin and platelet count abnormalities allowed clinicians to identify potential SICD earlier.…”
Section: Ai In Common Small Intestinal Diseasesmentioning
confidence: 99%